Diagnostic Ability of Dynamic Contrast-Enhanced Magnetic Resonance Imaging for Prostate Cancer and Clinically Significant Prostate Cancer in Equivocal Lesions: A Systematic Review and Meta-Analysis - Zeng, Jing; Cheng, Qingqing; Zhang, Dong; Fan, Meng; Shi, Changzheng; Luo, Liangping (Frontiers in Oncology, 2021)
Background: Dynamic contrast-enhanced magnetic resonance imaging (DCE-MRI) now has been used to diagnose prostate cnacer (PCa). Equivocal lesions are defined as PIRADS category 3 or a Likert scale of 1-5 category 3 lesions. Currently, there are no clear recommendations for the management of these lesions. This study aimed to estimate the diagnostic capacity of DCE-MRI for PCa and clinically significant prostate cancer (csPCa) in equivocal lesions. Materials and methods: Two researchers searched PubMed, Embase and Web of Science to identify studies that met our subject. We searched for articles that mention the accuracy of the diagnosis of DCE-MRI for PCa or csPCa in equivocal lesions and used histopathological results as the reference standard. We used a tool (the Quality Assessment of Diagnostic Accuracy Studies-2 tool) to evaluate the quality of the studies that we screened out. Meta-regression was used to explore the reasons for heterogeneity in results. Results: Ten articles were eventually included in our study. The sensitivity, specificity and 95% confidence intervals (CI) for DCE-MRI in diagnosing csPCa were 0.67 (95% CI, 0.56-0.76), 0.58 (95% CI, 0.46-0.68). The sensitivity and specificity and 95% CI for DCE-MRI in diagnosing PCa were 0.57 (95% CI, 0.46-0.68), 0.58 (95% CI, 0.45-0.70). The areas under the curve (AUC) of DCE-MRI were 0.67 (95% CI, 0.63-0.71) and 0.60 (95% CI, 0.55-0.64) while diagnosing csPCa and PCa. Through meta-regression, we found that study design, magnetic field strength, the definition of csPCa, and the scoring system were the sources of heterogeneity. Conclusion: The results of our study indicate that the role of DCE-MRI in equivocal lesions may be limited.